The effect of unity in sport teams on athletes' mental health: Investigating the mediating role of resilience - Yamada, K.; Kawata, Y.; Kamimura, A.; Hirosawa, M. (International Journal of Sport & Health Science, 2017)
Unity is one of the most important factors for individual and team performance in sports. Mental health is also identified an important factor for athletes' sports performance. Scholars have proposed that athletes' mental health is related to resilience, that includes environmental and personal factors. We have hypothesized that unity in sports teams predicts environmental and personal factors of resilience, which in turn relate to athletes' mental health. Therefore, the purpose of the present study was to this examine the effect of team unity on athletes' mental health, and the mediating effect of resilience in its relationship. A total of 626 university athletes (average age 20.08 ± 1.31 years) from 16 sports completed questionnaires. The survey questionnaire comprised the Unity Scale for Sports Teams (Yamada et al., 2013), the Psychological Resilience Scale for University Athletes (Ueno and Shimizu, 2012) and the General Health Questionnaire-30 (Nakagawa and Daibo, 1985). Relationships between team unity, resilience and mental health were tested, as well as the above hypothesis. Results showed that positive correlations between team unity, athletes' resilience and mental health. Additionally, the results supported the mediation hypothesis of resilience in the relationship between team unity and mental health. The results suggest that interventions aiming to support athletes' mental health should focus on both teams and individual athletes.